Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd002283.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Retention procedures for stabilising tooth position after treatment with orthodontic braces

Abstract: Retention procedures for stabilising tooth position after treatment with orthodontic braces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 29 publications
0
54
0
3
Order By: Relevance
“…The clinical effectiveness of different retainer designs has been subject to surprisingly few randomized controlled trials (Littlewood et al, 2006a(Littlewood et al, , 2006b. The available literature indicates that more settling, as measured by an increase in the number of occlusal contacts, is reported to occur with a Hawley-style retainer (Basciftci et al, 2007) than an Essix retainer (Sauget et al, 1997).…”
Section: Retentionmentioning
confidence: 99%
“…The clinical effectiveness of different retainer designs has been subject to surprisingly few randomized controlled trials (Littlewood et al, 2006a(Littlewood et al, , 2006b. The available literature indicates that more settling, as measured by an increase in the number of occlusal contacts, is reported to occur with a Hawley-style retainer (Basciftci et al, 2007) than an Essix retainer (Sauget et al, 1997).…”
Section: Retentionmentioning
confidence: 99%
“…The occurrence of failures in fixed retainers is highly variable [5][6][7], ranging from 31.7% to 5.9% [8][9][10][11][12][13]. Many studies in the literature have shown failures and unexpected tooth position changes, such as a torque difference between two adjacent mandibular incisors and an increased buccal inclination and movement of one mandibular canine [1].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of sufficient research data for evidence-based guidelines and the need for randomized clinical and in vitro studies were highlighted by the Cochrane Review published in 2006 [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present studies on the use of fixed retainers mainly concern the effectiveness, success and failure rate of a bonded retainer and oral hygiene aspects of different types of fixed retention. In the literature, there is one Cochrane review available summarizing the results of randomized and quasirandomized controlled trials on this topic [8]. The quality of trials on retention was not thorough enough for a true conclusion to be drawn.…”
Section: Introductionmentioning
confidence: 99%